2022
DOI: 10.2196/34790
|View full text |Cite
|
Sign up to set email alerts
|

Online Health Information Seeking Behaviors Among Older Adults: Systematic Scoping Review

Abstract: Background With the world’s population aging, more health-conscious older adults are seeking health information to make better-informed health decisions. The rapid growth of the internet has empowered older adults to access web-based health information sources. However, research explicitly exploring older adults’ online health information seeking (OHIS) behavior is still underway. Objective This systematic scoping review aims to understand older adults’… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 105 publications
3
85
1
Order By: Relevance
“…Therefore, the elderly are not unfamiliar with apps. A recent systematic revealed that older adults tend to use the Internet to search more disease-related health information than the adolescent and youth population [24]. Our study provided an app as a guiding tool for the elderly with sarcopenia to acquire accurate information in a convenient and low-cost approach [25].…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the elderly are not unfamiliar with apps. A recent systematic revealed that older adults tend to use the Internet to search more disease-related health information than the adolescent and youth population [24]. Our study provided an app as a guiding tool for the elderly with sarcopenia to acquire accurate information in a convenient and low-cost approach [25].…”
Section: Discussionmentioning
confidence: 90%
“…Proxy seekers also used the information to provide emotional [ 51 , 62 ] and material support, especially as informal caregivers [ 46 , 61 ] to the person. They used the information to change that person’s lifestyle; for example, mothers in 1 study cooked healthier food and encourage their families to walk together as a form of exercise [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…These surrogate OHI seekers were more likely to live with others and more likely to search on behalf of their partners, children, or other family members rather than for friends or colleagues [11]. This finding was echoed in several studies that reported that the proxy seeker was most often a member of the same household or with whom the person had close ties [12,15,[46][47][48][49][50][51].…”
Section: Characteristics Of Proxy Seekersmentioning
confidence: 96%
See 1 more Smart Citation
“…Given the results of the offline study and the barriers to access to information online that elderly people encounter, it can be concluded that the Internet should be more and more often used as a tool to educate on patient safety, but must not be the only such tool [ 24 ]. The results of the questionnaires show that elderly people always prefer other media, like radio and TV.…”
Section: Discussionmentioning
confidence: 99%